DEVELOPMENT OF FLIPBOOK MEDIA IN THE MATERIAL OF BASIC CONCEPTS OF HISTORY IN INDONESIA TO INCREASE STUDENT CREATIVITY IN SMK PGRI 2 SIDOARJO: Pengembangan Media Flipbook Dalam Materi Konsep Dasar Sejarah di Indonesia Untuk Meningkatkan Kreatifitas Siswa di SMK PGRI 2 Sidoarjo - J. Priyanto Widodo; Aulia Fitriany; Kartika Simanjuntak (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to develop digital learning media in the form of interactive flipbooks (Flipgames) to enhance students' creativity in history learning. The background of this study is the minimal use of digital media, which has resulted in low student engagement. Flipgames integrate multimedia elements (images, videos, audio, animations) with educational games (quizzes, puzzles, interactive challenges). The research used the R&D method with the Borg and Gall model and a descriptive quantitative approach, involving 10th grade students at SMK PGRI 2 Sidoarjo through observation, interviews, and questionnaires. The results of expert validation of the media (92%) and material (88%) showed high feasibility, while field trials received a positive response from 98.99% of students. The validity test showed that 13 of the 15 items were valid, and Cronbach's Alpha reliability of 0.812 indicated high consistency. The findings confirm that Flipgames are effective in increasing student creativity and engagement, with the novelty of integrating game-based learning in a digital flipbook format.